Fire resistance of composite slabs with steel deck: from experiments to numerical simulation - Piloto, P.A.G. (2020)
This work investigates the thermal insulation behaviour of composite slabs with steel deck under standard fire test conditions. This composite slab consists of a concrete topping cast on the top of a steel deck. The concrete is usually reinforced with a steel mesh on the top and may also be reinforced using individual rebars. The steel deck also acts as reinforcement and may be directly exposed to fire conditions. This composite solution is widely used in every type of buildings which require fire resistance, in accordance to regulations and standards. The fire rating of this type of elements is determined by standard fire tests. Two samples were tested using standard fire conditions ISO834 to evaluate the Integrity (E) and insulation (I). The scope of this investigation concerns the fire rating for insulation (I). Numerical thermal simulation was also developed using Matlab PDE toolbox and ANSYS to compare the results and to find out the thermal effects of standard fire exposure. The results are also compared with the simplified method proposed by Eurocode 4-part 1.2, which seems to be unsafe.